ASUHAN KEPERAWATAN PADA IBU HAMIL (G1P0A0) DENGAN PREEKLAMPSIA DI WILAYAH KERJA PUSKESMAS CIPUTAT KOTA TANGERANG SELATAN - Suci Pujawati (2023)
The purpose of this study is to monitor and prevent complications that may occur in the mother and fetus. The descriptive research aspect is an aspect of the research objectives used in compiling this research. The data collection method in this study is a qualitative research method by conducting interviews, observations, and documentation on Mrs. A directly using the assessment format and providing nursing care to pregnant women which the author will then use the SOAP method. The results of the study are within three days there is a decrease in the value of systole and diastole, where the condition of stage 1 hypertension (mild hypertension) is expected to progress to normal, therefore Mrs. A and her family who already understand and are able to realize it independently in accordance with the interventions that have been given and taught to patients to meet the achievement of normal blood pressure and the disappearance of some signs and symptoms of increased TIK.